DESIGNING COMMUNICATIVE TRAINING FOR TECHNOLOGY STUDENTS BASED ON PROFESSIONAL STANDARDS - Ryazapova, Liliya; Vjatkina, Irina; Kitaeva, Liudmila; Viugina, Sazida; Sirotkina, Olga; Slepneva, Elena (Revista Inclusiones, 2020)
The research topicality is due to the need to develop the basic educational programs of higher education taking into account the competences of professional standards while transiting to educational standards of the new generation. The paper is aimed at defining the main principles of projecting individual disciplines and blocks (modules), taking into account the normative basis of the actual federal educational standards. The key theoretical research methods for studying the problem of educational activities implementation in accordance with the updated requirements were analysis, summarization and modeling, which allowed comprehensive examination of the approaches to selecting and structuring the content of education. The empirical research methods included documents processing and introducing the results into pedagogical practice, which allowed carrying out the pedagogical experiment and training with groups of students. The article considers the possibility to use descriptors of labor actions as content basis for formulating the indices of developed competences. The need to elaborate an invariant core of curriculum was determined, which would unite training in different majors within the educational establishment, and a variation part, which would take into account the professional specificity, the individual demands of the learners, and the regional features. The principles of introducing the modules are proposed, which would form universal competences, in particular communicative ones, obligatory for the graduates. A comparative analysis of model educational programs of technical and technological profile was carried out. The possibility of uniting competence indices into basic groups was identified, the groups being compilation of scientific-professional texts, public speeches, carrying out discussions, and business correspondence. The authors propose a universal course, elaborated with the account of principles of selecting and structuring the content of professional training, which allowed forming the effective communicative competence of Master course graduates.